Clinical efficacy and safety of statin treatment after carotid artery stenting - Lingya Qiao; Shibo Wang; Qiang Jia; Ji Bian; Yimu Fan; Xiaolin Xu (Artificial Cells, Nanomedicine, and Biotechnology)
Objective The randomized controlled trail was carried out to investigate the influence of statin pre-treatment on clinical efficacy of carotid artery stenting (CAS).Methods 160 eligible patients were randomly divided into statin group (n = 82) and control group (n = 78). The patients in statin group received 40 mg atorvastatin daily 7 days before operation. Major endpoints included transient ischemic attack (TIA), stroke, death, myocardial infarction (MI), and other cardiac adverse events within 30 days after CAS.Results Preoperative baseline information was similar between the statin and control groups (p > 0.05 for all). Within 48 h after operation, the occurrence rate of CIN (3.66% vs 8.97%, p = .019) and new infarction (4.88% vs. 14.10%, p = .045) were significantly lower in statin group than in control group. 30 days after CAS, the incidences of TIA (12.20% vs. 26.92%, p = .018), ischemic stroke (6.10% vs. 16.67%, p = .034), and other cardiac complications (7.32% vs. 19.23%, p = .026) were also significantly lower in statin group, than in the control group. Multiple analysis demonstrated that statin use exerted protective effect against ischemic stroke (OR = 0.038, 95% CI = 0.003–0.543, p = .016) and other cardiac complications (OR = 0.208, 95%CI = 0.063–0.694, p = .011).Conclusion Pre-treatment with statin is an effective and safe strategy to prevent from perioperative complications and to improve postoperative outcomes in patients undergoing CAS.